Analysis of Bold Signals from Different Brain Regions in Healthy People and Stroke Patients Using Wavelet Entropy - Jara-Valencia, J (IEEE Computer Society, 2022)
Since its inception, the study of the human brain circulation has presented a number of challenges to researchers as it is a complex system that can be affected by multiple factors and diseases. Stroke is a disorder in which blood flow decreases considerably, or ceases completely, causing deterioration, and even death, of brain tissue due to lack of oxygen and nutrients. One method to observe cerebral hemodynamics is through a signal of the changes in residual oxygen that are occurring in the brain, which can be extracted from magnetic resonance images, that is known as the BOLD signal. This paper proposes an approach to analyze BOLD signals using Wavelet entropy, looking for differences between signals from stroke patients and control subjects. Significant differences could be obtained between the brain regions of patients affected by stroke, which warrants further investigation. © 2022 IEEE.